(untitled) (The Pakistan Development Review, 1999)
Like most developing countries, Pakistan has undertaken drastic economic policy reforms since the mid-1980s. Under these structural reforms there is a general shift away from quantitative restrictions and price controls towards liberalisation and privatisation. The empirical studies1 analysing the impact of the reforms report mixed results. Economy wide framework like Computable General Equilibrium (CGE), based on the social accounting matrix, is well suited to analysing the effect of these structural reforms. The CGE models are developed to capture the medium to long-run effects through which adjustment programmes affect income distribution. These models are often used to evaluate the effects of trade and tax policies on income distribution in developing countries. There are three interacting channels through which these adjustment policies affect income distribution, viz., the relative price effect, the asset price effect and the shift in portfolio. However, in this study, we are analysing the effect of changes in relative prices only.